A New Platform for Profiling Degradation-Related Impurities Via Exploiting the Opportunities Offered by Ion-Selective Electrodes: Determination of Both Diatrizoate Sodium and Its Cytotoxic Degradation Product. (23rd November 2019) - Riad, Safaa M; Abd El-Rahman, Mohamed K; Fawaz, Esraa M; Shehata, Mostafa A
Abstract: Although the ultimate goal of administering active pharmaceutical ingredients (APIs) is to save countless lives, the presence of impurities and/or degradation products in APIs or formulations may cause harmful physiological effects. Today, impurity profiling (i.e., the identity as well as the quantity of impurity in a pharmaceutical) is receiving critical attention from regulatory authorities. Despite the predominant use of spectroscopic and chromatographic methods over electrochemical methods for impurity profiling of APIs, this work investigates the opportunities offered by electroanalytical methods, particularly, ion-selective electrodes (ISEs), for profiling degradation-related impurities (DRIs) compared with conventional spectroscopic and chromatographic methods. For a meaningful comparison, diatrizoate sodium (DTA) was chosen as the anionic X-ray contrast agent based on its susceptibility to deacetylation into its cytotoxic and mutagenic degradation product, 3, 5-diamino-2, 4, 6 triiodobenzoic acid (DTB). This cationic diamino compound can be also detected as an impurity in the final product because it is used as a synthetic precursor for the synthesis of DTA. In this study, four novel sensitive and selective sensors for the determination of both DTA and its cytotoxic degradation products are presented. Sensors I and II were developed for the determination of the anionic drug, DTA, and sensors III and IV were developed for the determination of the cationic cytotoxic impurity. The use of these novel sensors not only provides a stability-indicating method for the selective determination of DTA in the presence of its degradation product, but also permits DRI profiling. Moreover, a great advantage of these proposed ISE systems is their higher sensitivity for the quantification of DTB relative to other spectroscopic and chromatographic methods, so it can measure trace amounts of DTB impurities in DTA bulk powder and pharmaceutical formulation without a need for preliminary separation.